Enantioselective synthesis of 3-fluoro-3-allyl-oxindoles via phosphine-catalyzed asymmetric γ-addition of 3-fluoro-oxindoles to 2, 3-butadienoates1. Issue 50 (25th June 2015) - Wang, Tianli; Hoon, Ding Long; Lu, Yixin
<x xml:space="preserve">Abstract</x> The first phosphine-catalyzed enantioselective γ-addition of 3-fluoro-oxindoles to 2, 3-butadienoates has been developed.